The nutcracker - Beddall, Fiona (London York press, 2020)
Uncle dresselmeyer is Clara's favourite uncle. one day, he visits Clare and her family. He has a prsent for Clare : a nutcracker, Clare loves the nutcracker and she goes downstairs in the night to see it again.but then a wind blows and the cupboard grows and then an army of mice march into the room to the toy cupboard "says the mouse king
English stories
1
Keywords: English stories